The Effect of Intellectual Capital Disclosure on the Cost of Equity in Islamic Banking : Pengaruh Intellectual Capital Disclosure Terhadap Cost of Equity pada Perbankan Syariah - Rini Pradianingsih; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study is to determine the effect of disclosure of intellectual capital in which there are variables of human capital, structural capital, and relational capital on the cost of equity in Islamic banking. The population determined in the study includes all Islamic banking companies registered with Bank Indonesia for the 2017-2019 period. The technique used for sampling in this research is purposive sampling technique. The types of data used in this study are earnings per share (EPS), book value per share (BVPS), stock prices and company disclosures regarding intellectual capital contained in the annual reports of Islamic banking. Sources of data obtained from the official website of each Islamic banking company. Data collection techniques were carried out using the documentation method. The data analysis technique used multiple regression analysis using a statistical tool in the form of SPSS version 25. The results of the study stated that human capital had no effect on the cost of equity, while structural capital and relational capital had an effect on the cost of equity.